Immunogenicity and duration of antibodies after vaccination with a two-dose series of the nine-valent human papillomavirus vaccine among Alaska Native children: a prospective cohort study - Jonathan Steinberg; Gitika Panicker; Elizabeth R. Unger; Ian Blake; Rayleen M. Lewis; Jesse Geis; Dana Bruden; Marc Fischer; Lauri E. Markowitz; Michael G. Bruce (BMC Infectious Diseases)
Abstract Background Human papillomavirus (HPV)-associated cancers are vaccine preventable. In 2016, the previously recommended three-dose HPV vaccination series was changed to a two-dose series and nine-valent HPV vaccine (9vHPV) became the only HPV vaccine available in the United States. Data on longer-term duration of antibodies following a 9vHPV two-dose series are limited. We evaluated the immunogenicity and duration of antibodies up to three years after vaccination with a two-dose series of 9vHPV in a cohort of Alaska Native children. Methods We enrolled Alaska Native children aged 9–14 years who received 9vHPV in Anchorage, Alaska during 2017–2018. We collected sera at six months after dose one and at one month, one year, and three years after dose two to measure type-specific immunoglobulin G (IgG) concentrations for the 9vHPV types (HPV6/11/16/18/31/33/45/52/58). Aggregate type-specific IgG concentrations were reported as geometric mean concentrations (GMC). Results A total of 227 children completed the two-dose series of 9vHPV and provided ≥ 1 blood sample. The median age at enrollment was 11.0 years (range: 9.0–14.6) and was similar between males and females (p = 0.11). At one month after dose two, all 197 participants with available serum were seropositive for all 9vHPV types. Among 145 participants who had a specimen available at three years after dose two, 134 (92%) remained seropositive for all 9vHPV types. GMC peaked for all types at one month post dose two and remained higher at three years post dose two compared to six months post dose one. Conclusions We found high immunogenicity and antibody persistence after a two-dose series of 9vHPV in this cohort of Alaska Native children. Further follow-up will determine duration of antibody detection in this cohort.